2020
DOI: 10.3390/ma13225226
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Properties and Low Cycle Fatigue of Sc-Modified AA2519-T62 FSW Joint

Abstract: The aim of this research was to examine the mechanical and fatigue properties of friction stir welded Sc-modified 5 mm thick AA2519-T62 extrusion. The joint was obtained using the following parameters: 800 rpm tool rotation speed, 100 mm/min tool traverse speed, 17 kN axial, and MX Triflute as a tool. The investigation has involved microstructure observations, microhardness distribution analysis, tensile test with digital image correlation technique, observations of the fracture surface, measurements of residu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…Compared to the base material, the tested joints have generally smooth fracture surfaces ( Figure 9 c,e). In both samples, the fracture mechanism is dominated by a transgranular ductile rupture, which is reflected in the mixed participation of large and fine dimples ( Figure 9 d,f) [ 40 ]. The locations of failure in these two samples are the same and the only difference is their microhardness: 100–105 HV0.1 in the case of S10 and 115 HV0.1 for F4.…”
Section: Resultsmentioning
confidence: 99%
“…Compared to the base material, the tested joints have generally smooth fracture surfaces ( Figure 9 c,e). In both samples, the fracture mechanism is dominated by a transgranular ductile rupture, which is reflected in the mixed participation of large and fine dimples ( Figure 9 d,f) [ 40 ]. The locations of failure in these two samples are the same and the only difference is their microhardness: 100–105 HV0.1 in the case of S10 and 115 HV0.1 for F4.…”
Section: Resultsmentioning
confidence: 99%
“…During the tests, it was observed that pin shape had a significant impact on the appearance of the joint produced as more material outflow on the retreating side of the joint was seen in joints made with the cylindrical threaded pin. Material outflow is a common defect [24,35,55]. The amount of outflow is associated with the shape of the pin and the process parameters [17,21,24].…”
Section: Comparison Of the Tool Pin's Shapementioning
confidence: 99%
“…The insufficient tool rotation speed (600 rpm) cause the settling of large X12Cr13 SS particles in the retreating side of the weldment and thereby reduces the joint strength. Also, this leads to the propagation of fracture along with the bimetallic interface in the nugget zone [20]. The lack of material movement is visible in the joint produced by 600 rpm due to the insufficient heat generated by the tool.…”
Section: Surface Morphology and Nugget Cross-section Of Iafsw Jointmentioning
confidence: 99%